A compatible printing advertising cloth based on Tyvek material and its preparation method and application

By combining the coating layer with the Tyvek layer with a specific component proportion, the problem that the existing Tyvek material advertising cloth is not compatible with multiple printing methods is solved, and compatibility with UV, weak solvent and Latex printing methods is achieved, and printing effect and light transmission performance are improved.

CN118581741BActive Publication Date: 2025-04-04WEIFANG UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410614059.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-04-04
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

The existing Tyvek material advertising cloth can only be compatible with UV printing, and cannot be compatible with weak solvent printing and Latex printing, which cannot meet the market's demand for compatible with multiple printing methods.

Method used

A compatible printing advertising cloth that combines the coating layer with a deionized water, acrylic latex and adsorbent with the Tyvek layer is adopted. Through specific component ratios and processing steps, the viscosity and dryness of the coating layer are suitable, and it can be compatible with three printing methods: UV, weak solvent and Latex.

Benefits of technology

It has achieved compatibility of Tyvek material advertising cloth with three printing methods: UV, weak solvent and Latex, significantly improved the printing effect and light transmission performance, and met the market's demand for diversified printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118581741B_ABST
    Figure CN118581741B_ABST
Patent Text Reader

Abstract

The present application discloses a compatible printing advertising cloth based on Tyvek material, and its preparation method and application, which belongs to the technical field of internal lighted advertising cloth. The compatible printing advertising cloth provided by the present application includes a coating layer and a Tyvek layer, and the coating layer includes the following components by weight: 10 to 20 parts of deionized water, 70 to 80 parts of acrylic latex, and 15 to 25 parts of adsorbent. The compatible printing advertising cloth is compatible with three printing methods: UV printing, weak solvent printing, and Latex printing, and has excellent printing effect and good light transmittance after lighting. The advertising cloth material has high color reproduction, excellent printing effect, and diversified color presentation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a compatible printed advertising cloth based on Tyvek material and a preparation method and application thereof, belonging to the technical field of internally-lit advertising cloth. Background Art

[0002] Tyvek material from DuPont is a non-woven fabric made of high-density polyethylene fiber through flash spunbonding. Its unique process makes it have high tear resistance and can withstand many times of continuous folding and bending without breaking. It has good durability and firmness, and is light in weight. Compared with paper of the same thickness and area, its weight is only about half of that of ordinary paper. Tyvek material is pure white and has two different structures: a hard structure material like paper and a soft structure material like cloth. This material has a wide range of uses and is often seen in various civilian designs and creative products, such as fashionable home furnishings, fashion, art, cultural and creative products, environmental protection and creative packaging, etc.

[0003] However, currently only a small amount of Tyvek is used for interior light advertising cloth on the market. There is only UV-printed Tyvek advertising cloth on the market, and there is no product that is compatible with three printing methods: UV printing, weak solvent printing, and Latex printing. In view of the current trend of Tyvek materials gradually replacing light box cloth in the market, and the advantages of Tyvek materials such as mildew resistance, moisture resistance, tear resistance and environmental protection can further enhance the market value, the development of a Tyvek advertising cloth that is compatible with various printing methods not only conforms to the current research direction and development trend, but also meets the latest needs of the current market. Summary of the invention

[0004] In order to solve the above problems, a compatible printing advertising cloth based on Tyvek material and a preparation method and application thereof are provided. The advertising cloth material provided in this application is compatible with three printing methods: UV printing, weak solvent printing and Latex printing, and has excellent printing effect and good light transmittance after lighting. The advertising cloth material has high color reproduction, excellent printing effect and diversified color presentation.

[0005] The present application provides a compatible printing advertising cloth based on Tyvek material, wherein the compatible printing advertising cloth comprises a coating layer and a Tyvek layer;

[0006] The coating layer comprises the following components by weight: 10 to 20 parts of deionized water, 70 to 80 parts of acrylic latex, and 15 to 25 parts of adsorbent.

[0007] Optionally, the acrylic latex includes 30 to 35 parts of acrylic latex A, 20 to 30 parts of acrylic latex B and 15 to 20 parts of acrylic latex C;

[0008] The glass transition temperature of the acrylic latex A is -12 to -8°C, the glass transition temperature of the acrylic latex B is -25 to -20°C, and the glass transition temperature of the acrylic latex C is 2 to 6°C.

[0009] Optionally, the adsorbent is a 13-17% solid content silica water dispersion, which is prepared by dispersing silica powder in water.

[0010] The main component of the adsorbent is silicon dioxide, which contains a porous structure that is conducive to matting and ink absorption, and will also affect the drying speed of printing. The solid content of the adsorbent will affect the content of silicon dioxide in the coating. If the solid content is too low, it will lead to slow drying and poor ink absorption. If the solid content is too high, the ink-absorbing coating layer will be prone to cracking and the ink layer will have poor adhesion.

[0011] Optionally, the particle size of the silicon dioxide powder is 5 to 20 μm.

[0012] According to another aspect of the present application, a method for preparing any of the above-mentioned Tyvek-based compatible printed advertising cloths is provided, the method comprising the following preparation steps:

[0013] S1. Prepare a coating layer: prepare deionized water, acrylic latex and adsorbent into an emulsion in proportion, and adjust the viscosity to 14-17s;

[0014] S2, coating the coating layer on the front side of the Tyvek layer and drying and curing at 70-80° C.;

[0015] S3. After drying in an oven, the compatible printed advertising cloth based on Tyvek material is obtained.

[0016] If the viscosity of the coating layer is too high, the fluidity of the coating will be poor, and the texture of the product will appear uneven and have cloud spots. If the viscosity of the coating layer is too low, the fluidity will be too good, which will lead to a small weight of the coating. A small weight will lead to low color and slow drying speed.

[0017] The melting point of Tyvek material is in the range of 110-140℃. When the temperature is higher than 90℃, it will deform. Therefore, the upper limit of the drying temperature is set at 90℃. Considering the protection of the material, the temperature is set at 70-80℃. In addition, the high speed will lead to a short stay in the oven, and the temperature needs to be increased appropriately. If the speed is slow and the stay in the oven is long, the temperature needs to be lowered appropriately. The overall temperature is controlled at 70-80℃. The dried product will not deform and has good flatness and high product stability.

[0018] Optionally, the coating layer is applied to the front side of the Tyvek layer by using a wire scraper.

[0019] The wire scraper coating method is easier to operate than the normal scraper coating method, and the material loading amount is large and stable during the coating process, and the spreadability is good. The normal scraper coating method will cause coating difficulties due to the low viscosity of the coating. For example, in the past, the coating viscosity was increased so that the coating could proceed normally, but its fluidity and spreadability would be affected by the high viscosity, resulting in uneven coating.

[0020] Optionally, the coating dry weight of the coating layer is 30-35 g / ㎡. During the coating process, the coating weight should be monitored in real time and the coating loading amount should be controlled to ensure the performance of the product. Specifically, the coating weight during the construction process is 90-110 g / ㎡ of wet material. According to the solid content of the coating tested, it is 33-36%. In fact, the dry material weight needs to be controlled at 30-35 g / ㎡ during the coating process.

[0021] Optionally, the vehicle speed is controlled at 10 to 12 m / min during the coating process. The vehicle speed should be controlled during the coating process. On the one hand, it can be coordinated with the coating temperature to ensure the coating effect of the coating layer during the coating process, and on the other hand, it can balance the thermal efficiency of drying and the production cost. In addition, it is necessary to pay attention to controlling the tension during the coating process. If it is too large, it is easy to tear the substrate, and if it is too small, it is easy to have ups and downs, resulting in uneven coating.

[0022] Optionally, 9 ovens are used in the drying step, and the temperatures of the 9 ovens are set to 40±2°C, 50±2°C, 60±2°C, 75±2°C, 75±2°C, 75±2°C, 75±2°C, 70±2°C, and 55±2°C, respectively. Setting the above drying temperatures can better solidify the coating. If the temperature is too low, the coating solidifies slowly, which will cause product adhesion during production. If the temperature is too high, the coating solidifies quickly, causing cracking of the coating.

[0023] According to the last aspect of the present application, there is provided a use of any of the above-mentioned Tyvek-based compatible printed advertising cloths in the production of backlit advertising boards.

[0024] The beneficial effects of this application include but are not limited to:

[0025] 1. The compatible printing advertising cloth based on Tyvek material according to the present application is compatible with three printing methods: UV printing, weak solvent printing and latex printing, and has excellent printing effect and good light transmittance presentation effect after lighting.

[0026] 2. The compatible printing advertising cloth based on Tyvek material according to the present application has high color reproduction, excellent printing effect, and diversified color presentation, and has good printing effect.

[0027] 3. According to the compatible printing advertising cloth based on Tyvek material of the present application, three different acrylic latexes with specific proportions and specific glass transition temperature ranges are formulated, so that the product feels harder, the cloth grain is clear and textured, it has good light transmittance, and has the advantages of good printing ink absorption and fast drying speed.

[0028] 4. According to the compatible printing advertising cloth based on Tyvek material of the present application, selecting a suitable silica particle size range has controlled the appropriate coating viscosity range of the coating layer, which can reduce the construction difficulty during the coating process and ensure the coating effect, so that the dried ink-absorbing coating layer has excellent ink absorption performance, bright colors and fast drying speed.

[0029] 5. According to the compatible printing advertising cloth based on Tyvek material of the present application, the appropriate coating temperature and drying temperature settings are adopted to ensure that the coating is smooth and stable during the coating process, and that the coating layer has good viscosity. After drying, the coating layer and the Tyvek layer have high stability. The ink-absorbing coating layer after drying feels hard and textured, with clear cloth grain, and has good printing effect and good light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0031] Figure 1 This is a picture of the Tyvek raw material involved in this application (A is without backlight, B is with backlight).

[0032] Figure 2 This is a diagram of the UV printing results of the advertising cloth in Example 1 of the present application (A is without backlight, B is with backlight).

[0033] Figure 3 This is a diagram of the weak solvent printing result of the advertising cloth in Example 1 of the present application (A is without backlight, B is with backlight).

[0034] Figure 4 This is the Latex printing result diagram of the advertising cloth in Example 1 of the present application (A is without backlight, B is with backlight).

[0035] Figure 5 The actual product effect of the advertising cloth in Example 1 of this application Figure 1 .

[0036] Figure 6 The actual product effect of the advertising cloth in Example 1 of this application Figure 2 .

[0037] Figure 7 The printing effect of Example 11 of the present application Figure 1 .

[0038] Figure 8 The printing effect of Example 11 of the present application Figure 2 .

[0039] Fig. 9 This is a graph showing the adhesion test results of the printing effect of Example 9 of the present application. DETAILED DESCRIPTION

[0040] The present application is described in detail below in conjunction with examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and catalysts in the examples of the present application are purchased through commercial channels.

[0041] In the present application, acrylic latex A was purchased from Shanghai Baolijia Chemical Co., Ltd. with the item number BLJ-720, acrylic latex B was purchased from Shanghai Baolijia Chemical Co., Ltd. with the item number BLJ-780A-2, and acrylic latex C was purchased from Shanghai Baolijia Chemical Co., Ltd. with the item number BLJ-7195. Other reagents and materials used in the present application can also be purchased commercially and are available to the public.

[0042] The present application scheme is described below through specific embodiments.

[0043] Example 1

[0044] The coating layer is composed of the following components in parts by weight: 15 parts of deionized water, 32 parts of acrylic latex A, 25 parts of acrylic latex B, 18 parts of acrylic latex C, and 20 parts of adsorbent; wherein the glass transition temperature of acrylic latex A is -10°C, the glass transition temperature of acrylic latex B is -23°C, the glass transition temperature of acrylic latex C is 4°C, and the adsorbent is a silica dispersion.

[0045] The preparation steps include: 1) preparing a silica dispersion, dispersing silica powder in water, adjusting the solid content to 15%, wherein the particle size of the silica powder is 5 to 20 μm. The specific operation is: adding 82 parts of deionized water into a stainless steel barrel, adding 2 parts of dispersant (sodium tripolyphosphate, sodium hexametaphosphate) and 15.5 parts of ultrafine silica powder in sequence during stirring, stirring and dispersing at a speed of 500 r / min for 20 minutes, and then adding 0.5 parts of defoaming agent (polydimethylsiloxane) and defoaming at a low speed of 250 r / min for 20 minutes to obtain an adsorbent.

[0046] 2) Prepare the coating layer, mix deionized water, acrylic latex and adsorbent into emulsion according to the proportion, adjust the viscosity to 16s, and measure it with a cup viscometer. The specific operation is: add 32 parts of acrylic latex A, 25 parts of acrylic latex B, 18 parts of acrylic latex C, and 5 thousandths of the total amount of dispersant in a stainless steel barrel through a 200-mesh filter, then stir at 300r / min for 10min, add 20 parts of adsorbent through a 200-mesh filter, stir at 300r / min for 10min, add a small amount (1-2 thousandths of the total amount) of defoamer to defoam, and finally add 15 parts of deionized water to adjust the coating viscosity to 15s.

[0047] 3) Use a wire scraper to apply the coating layer on the front of the Tyvek material and then dry it. The specific operation is: use a wire scraper to evenly apply the coating on the front of the Tyvek substrate, dry and solidify it at 75℃ to form an ink-absorbing coating layer. Coating speed: 11m / min, coating dry weight: 33g / ㎡, 9-section oven temperature: 40℃, 50℃, 60℃, 75℃, 75℃, 75℃, 75℃, 70℃, 55℃.

[0048] Example 2

[0049] The coating layer is composed of the following components in parts by weight: 10 parts of deionized water, 35 parts of acrylic latex A, 30 parts of acrylic latex B, 15 parts of acrylic latex C, and 25 parts of adsorbent; wherein the glass transition temperature of acrylic latex A is -12°C, the glass transition temperature of acrylic latex B is -20°C, the glass transition temperature of acrylic latex C is 2°C, and the adsorbent is a silica dispersion.

[0050] The preparation steps include: 1) preparing a silicon dioxide dispersion, dispersing silicon dioxide powder in water, adjusting the solid content to 17%, wherein the particle size of the silicon dioxide powder is 5 to 20 μm. The specific operation is: adding 82 parts of deionized water into a stainless steel barrel, adding 2 parts of dispersant (sodium tripolyphosphate, sodium hexametaphosphate) and 15.5 parts of ultrafine silicon dioxide powder in sequence during stirring, stirring and dispersing at a speed of 500 r / min for 20 minutes, and then adding 0.5 parts of defoaming agent (polydimethylsiloxane) and defoaming at a low speed of 250 r / min for 20 minutes to obtain an adsorbent.

[0051] Prepare the coating layer, mix deionized water, acrylic latex and adsorbent into emulsion in proportion, adjust the viscosity to 16s, and measure it with a cup viscometer. The specific operation is: add 32 parts of acrylic latex A, 25 parts of acrylic latex B, 18 parts of acrylic latex C, and 5 thousandths of the total amount of dispersant in a stainless steel barrel through a 200-mesh filter, then stir at 300r / min for 10min, add 20 parts of adsorbent through a 200-mesh filter, stir at 300r / min for 10min, add a small amount (1-2 thousandths of the total amount) of defoamer to defoam, and finally add 12 parts of deionized water to adjust the coating viscosity to 17s.

[0052] The coating layer is applied on the front of the Tyvek material by a wire scraper coating method and then dried. The specific operation is: the coating is evenly scraped on the front of the Tyvek substrate by a wire scraper coating method, and dried and cured at 70°C to form an ink-absorbing coating layer. Coating speed: 10m / min, coating dry weight: 35g / ㎡, 9-section oven temperature: 42°C, 52°C, 62°C, 77°C, 77°C, 77°C, 77°C, 72°C, 57°C.

[0053] Example 3

[0054] The coating layer is composed of the following components in parts by weight: 20 parts of deionized water, 30 parts of acrylic latex A, 20 parts of acrylic latex B, 20 parts of acrylic latex C, and 15 parts of adsorbent; wherein the glass transition temperature of acrylic latex A is -8°C, the glass transition temperature of acrylic latex B is -25°C, the glass transition temperature of acrylic latex C is 6°C, and the adsorbent is a silica dispersion.

[0055] The preparation steps include: 1) preparing a silicon dioxide dispersion, dispersing silicon dioxide powder in water, adjusting the solid content to 13%, wherein the particle size of the silicon dioxide powder is 5 to 20 μm. The specific operation is: adding 82 parts of deionized water into a stainless steel barrel, adding 2 parts of dispersant (sodium tripolyphosphate, sodium hexametaphosphate) and 15.5 parts of ultrafine silicon dioxide powder in sequence during stirring, stirring and dispersing at a speed of 500 r / min for 20 minutes, and then adding 0.5 parts of defoaming agent (polydimethylsiloxane) and defoaming at a low speed of 250 r / min for 20 minutes to obtain an adsorbent.

[0056] Prepare the coating layer, mix deionized water, acrylic latex and adsorbent into emulsion in proportion, adjust the viscosity to 16s, and measure it with a cup viscometer. The specific operation is: add 32 parts of acrylic latex A, 25 parts of acrylic latex B, 18 parts of acrylic latex C, and 5 thousandths of the total amount of dispersant in a stainless steel barrel through a 200-mesh filter, then stir at 300r / min for 10min, add 20 parts of adsorbent through a 200-mesh filter, stir at 300r / min for 10min, add a small amount (1-2 thousandths of the total amount) of defoamer to defoam, and finally add 17 parts of deionized water to adjust the coating viscosity to 14s.

[0057] The coating layer is applied on the front of the Tyvek material by a wire scraper coating method and then dried. The specific operation is: the coating is evenly scraped on the front of the Tyvek substrate by a wire scraper coating method, and dried and cured at 80°C to form an ink-absorbing coating layer. Coating speed: 12m / min, coating dry weight: 30g / ㎡, 9-section oven temperature: 38℃, 48℃, 58℃, 73℃, 73℃, 73℃, 73℃, 68℃, 53℃.

[0058] Example 4

[0059] This embodiment is substantially the same as Embodiment 1, except that the acrylic latex contains only 75 parts of acrylic latex A.

[0060] Example 5

[0061] This embodiment is substantially the same as Embodiment 1, except that the acrylic latex contains only 75 parts of acrylic latex B.

[0062] Example 6

[0063] This embodiment is substantially the same as Embodiment 1, except that the acrylic latex contains only 75 parts of acrylic latex C.

[0064] Example 7

[0065] This embodiment is substantially the same as the embodiment 1, except that the acrylic latex comprises 35 parts of acrylic latex A and 35 parts of acrylic latex B.

[0066] Example 8

[0067] This embodiment is substantially the same as the embodiment 1, except that the acrylic latex only contains 35 parts of acrylic latex A and 35 parts of acrylic latex C.

[0068] Example 9

[0069] This embodiment is substantially the same as the embodiment 1, except that the acrylic latex only contains 35 parts of acrylic latex B and 35 parts of acrylic latex C.

[0070] Example 10

[0071] This embodiment is basically the same as the embodiment 1, except that the particle size of the silicon dioxide powder is 25 to 30 μm.

[0072] Embodiment 11

[0073] This embodiment is basically the same as embodiment 1, except that the coating viscosity is adjusted to 20s.

[0074] Example 12

[0075] This embodiment is basically the same as embodiment 1, except that the coating viscosity is adjusted to 10s.

[0076] Comparative Example 1

[0077] As attached Figure 1 As shown in the figure, it is Tyvek raw material. This Tyvek raw material is not compatible with UV printing, weak solvent printing and Latex printing at the same time. In addition, there is only Tyvek advertising cloth that can be printed with UV on the market. There is no product that is compatible with UV printing, weak solvent printing and latex printing at the same time. Figure 1 The Tyvek raw material is also not compatible with UV printing, weak solvent printing and latex printing.

[0078] Experimental Example 1

[0079] The glass transition temperature of the acrylic latex used was tested. The following samples were tested for the same conditions as in Example 1 except that the glass transition temperature was different from that in Example 1.

[0080] Table 1 Glass transition temperature of acrylic latex in the test samples

[0081]

[0082] Test samples 1 to 6 in Table 1 were tested and compared with the results of the products in Examples 1 to 3. The results are shown in Table 2 below.

[0083] Table 2 Comparison results of test examples 1 to 3 and test samples 1 to 6

[0084]

[0085]

[0086] According to the results in Table 2, the three acrylic latexes with different glass transition temperatures have a synergistic effect. The three acrylic latexes with different properties can coordinately adjust the product's soft and hard feel, light transmittance, printing ink absorption performance and drying speed. Acrylic latexes with different glass transition temperature properties have different product performances when used together. Compared with test samples 1 to 6, the products of Examples 1 to 3 of the present application have a harder feel and clear texture, good light transmittance, good printing ink absorption effect and fast drying speed.

[0087] Test Example 1

[0088] The products prepared in Examples 1 to 12 were tested, focusing on the compatibility of each product with three types of printing, printing effect and light transmittance. In addition, the adhesion and feel of the coating layer were also evaluated. The test results are shown in Table 3 below.

[0089] Table 3 Performance test results of products in Examples 1 to 12

[0090]

[0091]

[0092]

[0093] According to the results in Table 3, the components in the coating layer work synergistically, and adjusting one of them will also have a certain impact on the effects of other components, resulting in changes in the performance of the final product, such as affecting the softness and hardness of the latex and the clarity of the texture, and also affecting the printing effect. The main function of the adsorbent is to absorb ink and quickly dry the ink layer, while the viscosity of the coating layer mainly affects the uniformity of the coating and the difficulty of implementing the coating process.

[0094] According to the comparison between the results of Examples 4 to 9 and Example 1, it can be seen that in the present application scheme, three acrylic latexes with a specific range of glass transition temperatures are selected in a specific ratio for compatibility. The obtained product is compatible with three printing methods, and has good ink absorption, bright colors, and fast drying speed. In addition, it also has excellent light transmittance and good adhesion of the coating layer. After being fixed and dried, it has good stability with the Tyvek layer, and the adhesion with the printing material during printing is also better, while the products of Examples 4 to 9 have different types of defects. According to Example 10, it can be seen that the particle size of the silica powder will affect the ink absorption performance and drying speed, so it has a relatively large impact on the printing performance. According to the results of Examples 11 and 12, it can be seen that the viscosity of the ink-absorbing coating layer affects the coating process and the coating effect. If the viscosity range is not appropriate, it will affect the implementation of the coating process, resulting in poor coating effect and also affecting the printing effect, such as poor ink absorption performance, color difference, low color density and slow drying speed.

[0095] like Figure 7 As shown, this is a picture of the printing effect of Example 11, with poor color and low color density; Example 11 absorbs ink poorly and dries slowly during the printing process, and the printing result is as follows Figure 8 As shown in the figure; since one side of the coating layer needs to be fixed to the Tyvek layer and the other side needs to be fixed to the printing material, its adhesion has a great influence on the quality of the product. Fig. 9 The adhesion test results of Example 9 are shown, and it can be seen that the adhesion of the product of Example 9 is very poor.

[0096] Test Example 2

[0097] Take the compatible printing advertising cloth prepared in Example 1, and perform UV printing, weak solvent printing and Latex printing respectively. The printing results are shown in the attached figure. Figure 2 , 3 As shown in Figure 4, A is a backlight-free state, and B is a backlight-on state. It can be seen that the compatible printing advertising cloth provided by this application is compatible with three printing methods: UV printing, weak solvent printing and Latex printing. Figure 5 and 6 The actual product renderings produced using the compatible printed advertising cloth show that the compatible printed advertising cloth still has good light transmittance after printing. It not only has good printing effects but also has excellent light transmittance. It is suitable for making advertising boards with backlights and has good publicity and display effects.

[0098] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A compatible printing advertising cloth based on Tyvek material, characterized in that: The compatible printing advertising cloth comprises a coating layer and a Tyvek layer; The coating layer comprises the following components by weight: 10 to 20 parts of deionized water, 70 to 80 parts of acrylic latex, and 15 to 25 parts of an adsorbent; The acrylic latex comprises 30 to 35 parts of acrylic latex A, 20 to 30 parts of acrylic latex B and 15 to 20 parts of acrylic latex C; the glass transition temperature of the acrylic latex A is -12 to -8°C, the glass transition temperature of the acrylic latex B is -25 to -20°C, and the glass transition temperature of the acrylic latex C is 2 to 6°C; The adsorbent is a silicon dioxide aqueous dispersion with a solid content of 13-17%, which is prepared by dispersing silicon dioxide powder in water; the particle size of the silicon dioxide powder is 5-20 μm.

2. The method for preparing a compatible printing advertising cloth based on Tyvek material according to claim 1, characterized in that: The preparation method comprises the following preparation steps: S1. Prepare coating layer: prepare deionized water, acrylic latex and adsorbent into emulsion according to proportion, and adjust viscosity to 14-17s; S2, applying the coating layer on the front side of the Tyvek layer and drying and curing at 70-80° C.; S3. After drying in an oven, the compatible printed advertising cloth based on Tyvek material is obtained.

3. The preparation method according to claim 2, characterized in that: The coating layer is applied on the front side of the Tyvek layer by using a wire blade.

4. The preparation method according to claim 2, characterized in that: The coating dry weight of the coating layer is 30-35 g / ㎡.

5. The preparation method according to claim 2, characterized in that: During the coating process, the vehicle speed is controlled at 10-12 m / min.

6. The preparation method according to claim 2, characterized in that: Nine ovens are used in the drying step, and the temperatures of the nine ovens are set to 40±2°C, 50±2°C, 60±2°C, 75±2°C, 75±2°C, 75±2°C, 75±2°C, 70±2°C, and 55±2°C, respectively.

7. Use of the compatible printed advertising cloth based on Tyvek material as claimed in claim 1 in making backlit advertising boards.

Citation Information

Patent Citations

  • Silver halide photographic sensitive material

    JP2001117202A

  • KR1018217740000B1